Synthesis, Growth and Characterization of Bis Thiourea Sodium Zinc Sulphate Single Crystals-A Semi Organic Nlo Material - Uma, K; Manimekalai, R; Pasupathi, G (International Journal of Chemistry and Materials Research, 2015)
The slow evaporation of the solvent technique is used to grow transparent nonlinear optical (NLO) single crystals of bis thiourea sodium zinc sulphate (BTSZS). The grown crystal is characterized by single crystal X-ray diffraction analysis to confirm the crystallization of the synthesized materials and to determine its unit cell parameters. The crystalline nature and purity of the grown crystals are confirmed by powder X-ray diffraction pattern. The FT-IR and FT-Raman spectra are recorded to identify the functional groups present in BTSZS crystals. The UV-VIS-NIR transmission spectrum of BTSZS crystals are recorded in the wavelength range 190 - 1100 nm to determine the lower cut-off wavelength, percentage of the transmittance and the optical constants such as bandgap, refractive index, extinction coefficient, reflectance etc., Fluorescence study confirms the green emission of BTSZS which indicates the grown crystal is well suited for NLO applications. The thermo gravimetric analysis and differential thermal analyses are used to identify the melting point and the thermal stability of the grown crystals. The second harmonic generation efficiency is measured by Kurtz powder method and it is found to be 1.3 times that of potassium dihydrogen orthophosphates (KDP).